Is Optimal Cytoreduction Post Neoadjuvant Chemotherapy the Only Prognostic Factor in Advanced Ovarian Cancer? - Dhiman, Pravesh; Bapsy, P.P.; Patil, C.N.; Raghupathi, Renu (South Asian Journal of Cancer, 2022)
Background Epithelial ovarian cancer (EOC) is one of the leading causes of cancer-related death in women. Approximately 70% of patients with EOC are diagnosed in advanced stage [The International Federation of Gynecology and Obstetrics(FIGO stage III and IV)] with an expected 5-year survival rate of 30%. Numerous studies have shown that survival with neoadjuvant chemotherapy (NACT) followed by interval debulking surgery (IDS) is noninferior to primary debulking surgery followed by chemotherapy.Materials and Methods In this retroprospective observational study, 50 patients with advanced ovarian cancer, diagnosed from January 2012 to January 2015, were included and followed-up till January 2017. Correlation of NACT with patient profile, CA125 levels, clinicopathologic parameters, progression-free survival (PFS), and treatment response was studied. Statistical analysis was performed using log-rank test and Kaplan-Meir survival plots.Results The extent of cytoreduction significantly correlated with PFS. The PFS was maximum in patients who had optimal cytoreduction (19 months) and 10 months in patients with suboptimal cytoreduction with p-value < 0.05. The survival was not significantly correlated with other parameters such as age, stage, preoperative CA125 levels, and ascites.Conclusions The extent of cytoreduction following NACT in this study was associated with statistically significant PFS advantage in patients who were able to undergo optimal cytoreduction, but not significantly correlated to other factors such as age, stage, preoperative CA125 levels, and ascites. NACT followed by interval cytoreduction is an important modality affecting survival in advanced EOC. Further studies and longer follow-up are needed to demonstrate survival advantage over standard treatment.
Keywords: epithelial ovarian cancer; cytoreductive surgery; interval debulking surgery; neoadjuvant chemotherapy; progression-free survival